Colloidosome based on Nanohydroxyapatite - Elizondo Vargas, Mariana (2025)
A protocol for the preparation of fatty acid-functionalized nanohydroxyapatite was developed. These nanoparticles were characterized and used as building blocks for the preparation of Pickering water-in-oil emulsions, which in turn were used as a template for colloidosomes. It is possible to encapsulate proteins in these structures, and their low cellular toxicity was also demonstrated. These structures show structural fragility to pH and temperature changes.